Impact of Interest Rate, Inflation and Gross Domestic Product to Demand for Property Credit in Indonesia - Putra, Ivan Pradana; Wasiaturrahma, Wasiaturrahma (Jurnal Ilmu Ekonomi Terapan, 2021)
An increase in credit, especially consumption credit, can trigger aggregate demand growth above potential output which causes the economy to heat up. This study aims to analyze the effect of macroeconomic variables, such as interest rates, inflation, and gross domestic product (GDP), on the demand for property credit in Indonesia with the period January 2011 – December 2018. The results show that in the short term, the interest rate lag 1 and lag 2, inflation lag 1, and GDP significantly influence the demand for peoperty credit. While, in the long term, only the interest rates and GDP significantly influence to the demand for property credit. Keywords: Property Credit, Interest Rates, Inflation, GDP, ARDL  JEL: C22, E51, G21